Implementation Of Dice Games In Improving Numerication Ability - Pradana, Pascalian Hadi; Romadhoni, Masruroh; Ali, A. Zulkarnain (FKIP Universitas Halu Oleo, 2024)
Early Childhood Education (PAUD) is the initial stage in the education system, where children are in the preschool period aged 0 to 6 years, which is a period of very rapid development. The purpose of this research is to determine the improvement in children's numeracy skills through the application of dice games. Early childhood numeracy skills include understanding and using basic mathematical concepts such as number recognition, simple counting, and object grouping. Numeracy skills help children develop cognitive, logical, and problem-solving abilities, which are important foundations for more complex mathematics learning in the future. Dice games make it easier for children to remember the material, especially in developing cognitive aspects by introducing simple counting methods. This study uses the Classroom Action Research (CAR) method, which involves two cycles where each cycle includes the stages of planning, implementation, observation, and reflection. Based on the results of the Classroom Action Research (CAR) and the data analysis conducted, it is concluded that dice games can improve children's numeracy skills. This is evidenced by the improvement in research results from cycle I, where 7 children or 43.75% met the minimum criteria for developing as expected, increasing to 14 children or 87.5% in cycle II. Because in cycle II the success indicators have been met, this research is declared complete. With those results, since the success indicators were met in cycle II, the research is considered complete.